The Production of Hydrogen from Aluminum Waste by Aluminum-Water Methods at Various Conditions. (November 2019) - Rohendi, D; Rachmat, A; Syarif, N; Said, M; Rihsansah, I
Abstract: The production of hydrogen gas from aluminum waste by Aluminum-water methods at various condition has been successfully performed. The hydrogen production is a very important for support the fuel cell application Hydrogen was produced both in the acidic and base conditions at various temperature and using lithium as the activator. The urgencies in this research were effective and cheaper methods. The highest hydrogen production from reaction 0.3 g aluminum with 30 mL hydrochloric acid 2 M at 50 °C in 10 minutes was 348 mL. Meanwhile, the best condition for aluminum water methods for 0.3 g of Aluminum as reactants, were 3 mL water, 5% w/w lithium content and 100 mesh aluminum particle size. Furthermore, using KOH as a catalyst, gave hydrogen product 670 mL with the rate at 67 mL/min.